Using Seesaw Application in Improving English Speaking Skills: the Case of an International Middle School (Journal of Contemporary Educational Policies and Practices, 2022)
This study is designed to identify factors affecting the 6th grade Korean students’ English speaking learning as well as the difficulties they encountered and then investigate the impacts of SeeSaw on speaking skills at an international middle school in Hanoi. In this study, the students’ improvements on speaking skills were measured by a pre-test and a post-test after the intervention. In order to address the factors causing the students’ difficulties in speaking, their learning motivation, interactions with teachers, peers and parents, and attitudes towards SeeSaw, 20 post-intervention questionnaires were delivered to the 20 students belonging to the experimental group. The questionnaire result analysis with SPSS also provided qualitative data on the social well-being of the Korean students. Furthermore, qualitative data taken from the interview with some random respondents were used to make the results obtained from the questionnaires clearer and more reliable. The study results revealed the students’ difficulties in learning English speaking skills and some enhancement in their speaking skills. It can be concluded that SeeSaw is a useful tool for the teaching and learning English speaking skills.